Tensiones entre la condicionalidad del Oportunidades y las ideas de responsabilidad y reciprocidad que le subyacen - Sandoval, Benjamín (El Colegio de México, 2015)
Based on an analysis of official documents and statements by different actors involved in the design and operation of Oportunidades Program, this article attempts to show the tensions between the conditionality applied in the Program and the theoretical and normative foundations of responsability and reciprocity (ideas) that lie behind it. Although this ideas justify the use of conditionality, as well they impose minimal restrictions and conditions that a society must fulfill so that its imposition doesn’t create injustice, especially for the poor. Mexico, as will be shown, doesn’t fulfill the minimal conditions of a fair society so that, in the light of these ideas, the conditionality implemented by the Oportunidades Program isn’t legitimate nor rational.